Jawabanmu

2013-12-11T11:21:43+07:00
Pembuktiannya dari kanan ke kiri aja ya
2\cos \alpha.\cos \beta=\cos (\alpha +\beta)+\cos (\alpha -\beta)

4.\cos x. \cos 2x. \cos 3x
=2(2.\cos x. \cos 2x). \cos 3x
=2(\cos (x+2x)+ \cos (x-2x)). \cos 3x
=2(\cos (3x)+ \cos (-x)). \cos 3x
=2.\cos (3x). \cos 3x + 2.\cos (-x). \cos 3x
=(\cos (3x+3x)+\cos (3x-3x))+(\cos (-x+3x)+\cos (-x-3x))
=\cos (6x)+\cos (0)+\cos (2x)+\cos (-4x)

\cos (0)=1  dan \cos (-\theta)=\cos \theta

=\cos 6x+1+\cos 2x+\cos 4x
=1+\cos 2x+\cos 4x+\cos 6x
klo bs sih, pilih jg sebagai jawaban "terbaik" hehehe